2020
DOI: 10.1136/bmjopen-2020-038988
|View full text |Cite
|
Sign up to set email alerts
|

Prospective cohort protocol examining the perioperative indicators for complications and early mortality following hip fracture surgery in the frail patient

Abstract: IntroductionThe primary aim is to validate earlier suggested risk factors and to find new associated risk factors for (30-day) mortality after a hip fracture in the frail population. The secondary aim is to determine the factors associated with perioperative complications. At last we want to develop and validate a more specific 30-day mortality prediction tool compared with the Nottingham Hip Fracture Score. The 30-day mortality prediction can help inform surgical risk and guide shared decision-making among pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…A detailed overview of the data collection and the standards of hip fracture treatment is available in the FAMMI study protocol. 17 The 30-day time frame was chosen based on the commonly used follow-up period by studies evaluating the association between perioperative mortality and a hip fracture. 8–10
Figure 1 Flow chart of included patients.
…”
Section: Methodsmentioning
confidence: 99%
“…A detailed overview of the data collection and the standards of hip fracture treatment is available in the FAMMI study protocol. 17 The 30-day time frame was chosen based on the commonly used follow-up period by studies evaluating the association between perioperative mortality and a hip fracture. 8–10
Figure 1 Flow chart of included patients.
…”
Section: Methodsmentioning
confidence: 99%
“…This study is an observational cohort study with real-time registration of patients in a prospective hip fracture database (FAMMI trial). 27 All consecutively admitted patients between 1 January 2018 and 11 January 2021 in two level II trauma teaching hospitals located in Rotterdam, the Netherlands, with fractures of the femoral neck and (sub)trochanteric area and an age of ≥ 65 years who were treated with osteosynthesis (i.e. cannulated screws, sliding hip screw, or cephalocondylar nail system) or prosthesis (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Hip fracture in elderly patients is a health problem with high morbidity and mortality. Studies have found that mortality in hip fractures within 30 days is 5-13% and 1-year mortality is 22-30% (1). The incidence of coronary artery disease, heart failure, atrial fibrillation and stroke increases significantly in elderly patients.…”
Section: Introductionmentioning
confidence: 99%